Improving Road Safety Governance through Public Service Innovation - Dede Mirza; Fitra Hadi Khaz; Refdi Refdi (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2024)
This study explores how public service innovations in motor vehicle testing, based on Regional Public Service Agencies (BLUD), can improve road safety governance. In regions with rapidly growing motor vehicle populations, inadequate roadworthiness controls contribute to high traffic accident risks. While Indonesia has a regulatory framework for motor vehicle testing, service delivery remains largely administrative and lacks a strong focus on road safety. The study aims to assess how public service innovations can enhance road safety governance through local government-managed vehicle testing based on BLUD. Using a qualitative case study approach, data were collected through in-depth interviews, observations, and document analysis involving local government officials, testing technicians, and service users. Thematic and interpretive data analysis identified governance dimensions that influence service effectiveness. The study finds that road safety governance improvement relies on four main capacities: relational, structural, resource, and adaptive. Although BLUD-based management offers flexibility for service innovation, its implementation has not fully aligned with road safety goals. Challenges remain in public trust, cross-agency coordination, resource availability, and organizational learning. The study concludes that integrating public service innovation with institutional capacity building and safety-focused performance management is essential for strengthening road safety governance. These findings highlight the strategic importance of motor vehicle testing in enhancing road safety and public value at the regional level.